'Inflammatory myofibroblastic tumour'‐like dedifferentiation of anaplastic lymphoma kinase‐rearranged lung adenocarcinoma. Issue 3 (27th April 2016) - Mason, Emily F; Fletcher, Christopher D M; Sholl, Lynette M
Abstract : Aims: Anaplastic lymphoma kinase (ALK) functions as an oncogenic driver in a subset of haematopoietic, epithelial and mesenchymal neoplasms. Activation of ALK most commonly occurs through gene fusion events, the presence of which predicts response to ALK‐targeted inhibitors in some tumour types. Echinoderm microtubule‐associated protein‐like 4 ( EML4 )– ALK fusions represent the majority of ALK rearrangements in lung adenocarcinomas and were, until recently, thought to be exclusive to that tumour type. However, recent work has identified EML4–ALK fusions in 20% of inflammatory myofibroblastic tumours (IMTs), particularly in those arising in the lung. Here, we present a patient with an ALK ‐rearranged poorly differentiated lung adenocarcinoma with a predominant sarcomatoid component that was morphologically indistinguishable from IMT. Methods and results: Targeted next‐generation sequencing revealed EML4 – ALK rearrangements in both components, with identical fusion sequences. Copy number analysis demonstrated focal gain of the MYC gene in the IMT‐like component. The findings support a diagnosis of ALK ‐rearranged lung adenocarcinoma with IMT‐like dedifferentiation. Conclusions: Our findings suggest that ALK‐driven epithelial and mesenchymal neoplasms exist on a morphological spectrum, and emphasize the need to consider translocation testing in pulmonary tumours with unusual sarcomatoid morphology.